The influence of networks and decision-making orientation on value creation in technology-based entrepreneurial businesses - T. Stanley van den Heever; Elmarie Venter (South African Journal of Business Management, 2019)
Background: Technology-based entrepreneurial businesses (TBEBs) have been identified as major contributors to economic growth and job creation in most global economies.Aim: The objective of this study was to empirically test the relationships between structured and unstructured networks and perceived value creation in 313 TBEBs, taking into account their decision-making orientation.Setting: TBEBs in the South African were identified and information was gathered through structured questionnaires.Methods: After an exploratory factor analyses (EFA), Cronbach's alpha coefficients were calculated to confirm the validity and reliability of the measuring instrument. Structural equation modelling (SEM) was the main statistical procedure used to test the significance of the relationships hypothesised between the various independent, mediating and dependent variables.Results: The main finding of the study was that TBEBs can create financial and non-financial value by adopting a decision-making orientation in the business to co-create the future with other stakeholders.Conclusion: In conclusion this study found that establishing both structured and unstructured networks enhances a co-creation decision-making orientation and contributes to value creation in TBEBs.
Keywords: 650